Incorporation of Bone Morphogenetic Protein-2 and Osteoprotegerin in 3D-Printed Ti6Al4V Scaffolds Enhances Osseointegration Under Osteoporotic Conditions - Wang, Xianggang; Li, Zhengyan; Wang, Zhonghan; Liu, He; Cui, Yutao; Liu, Yuzhe; Ren, Ming; Zhan, Hongsheng; Li, Zuhao; Wu, Minfei; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2021)
Osteoporosis is an age-related metabolic disease which has limited bone regeneration capacity and pathological excessive osteoclast activity. After arthroplasty in patients with osteoporosis, poor interface osseointegration due to insufficient bone regeneration ability often leads to catastrophic complications such as prosthesis displacement and loosening, and periprosthetic fractures. In this study, we prepared a thermosensitive hydrogel loaded with bone morphogenetic protein-2 (BMP-2) to promote osteogenesis and osteoprotegerin (OPG) to inhibit the excessive osteoclast activity. In order to construct three-dimensional (3D) printed bioactive interface for implantation, the drugs loaded hydrogel was injected into porous Ti6Al4V scaffolds. The 3D printed bioactive interface showed good biocompatibility and sustained released of BMP-2 and OPG for more than 20 days. In vitro experiments indicated that composite bioactive interface promoted osteogenic differentiation and reduced the osteoclastic differentiation of osteoporosis-derived bone marrow mesenchymal stem cells (OP-BMSCs), simultaneously. Remarkably, immunofluorescence staining, Micro-CT, histological, and biomechanical tests demonstrated that the cooperation of sustained release of BMP-2 and OPG from the bioactive interface significantly improved bone ingrowth and osseointegration in osteoporotic defects. In conclusion, this study demonstrated the BMP-2 and OPG incorporated 3D printed bioactive interface can serve as a potential strategy to promote osseointegration for osteoporotic patients after joint replacement.